ANALISIS SEMIOTIK LIRIK LAGU “GOSIP JALANAN” DARI GRUP MUSIK SLANK - Yulita Karatem; Pamerdi Giri Wiloso; John R Lahade (Universitas Kristen Satya Wacana, 2013)
The song is an expression of the writer to the listener, based on exprerience, gained either from oneself, others as well as the environment. A song contains lyrics that use language to convey the intention or purpose of the writer to the listener. Slank is a rock and roll music group in Indonesia. Slank is more familiar with the anti-corruption movement or part of social criticism. One of its songs entitled “Gosip Jalanan” gets a lot of response from various parties. Members of the Parliament consider the lyrics to be an insult to their perfomance as the people’s representatives, so through their Honorary Council, they were about to take a legal action against Slank. However the general public supported the music group as they considered songs created by Slank depicted reality.This study employed a semiotic analysis method aimed at exlpaining the meaning of each sign found in the lyrics from the writer’s as well as the listeners’ point of view in relation to their respective socio-cultural backgrounds.The results of this study revealed that “Gosip Jalanan” lyrics served as an expression of Slank music group’s contemplation based on the members’ personal experience and observation of variety of social realities amidst the society. Corruption and different forms of power abuse currently prevailing in Indonesia the group judged as having been done on a massive and systematic scale, by which Slank referred to as the “mafia”. Money became the source of power misused by the mafia to such extent that they were able to overrun the existing law and regulations. Meanwhile the people listening to the lyrics responded differently. Some were in agreement but others in disagreement about the meaning conveyed by the lyrics. The former judged the lyrics to be in accordance with reality the song attempted to depict, whereas the latter considered that the song did not depict reality, as it was only partial and not universal in nature. Key Words: Music, Lyrics, Sign and Meanings, Semiotics